Advocating for the Health Worker - Melissa McDiarmid (Ubiquity Press, 2019)
Background: Health workers in both well-resourced and limited income settings face health threats from exposures encountered in their unique and complex work environment. Even before the 2014 Ebola outbreak, preventable harm was routinely felt by health workers, most visibly through the fatal collusion between the HIV/AIDS epidemic and tuberculosis (TB) infection in high endemic countries. Objectives: The aim of this paper is to examine the analyses of the health sector workforce by development and public health agencies regarding its sustainability, threats from workersʼ personal health risks and discussion of protections to address those risks. Methods: Development and public health agency reports assessing the sustainability of and threats to the health workforce both pre-and post the 2014 Ebola outbreak were examined with a focus on low and middle- income countries (LMICs). Findings: Reviews of the health sector workforce have largely focused on its role as a necessary component of sustainable development. Hence, staff competency, numbers and productivity have been emphasized with little notice of the conditions of work and the highly hazardous environment contributing to worker out-migration, illness and death. Conclusions: Going forward, the 2016 World Health Assembly campaign to advance human resources for health and other UN efforts on health employment may offer some opportunities to address needed health worker protections. However, to these largely competency-focused workforce development efforts must 'first' be brought resources for and commitment to protecting the safety of these workersʼ lives and livelihood. Doing less defeats investments in fragile health systems and is plainly unethical.